Transcranial direct current stimulation and neuroplasticity genes: implications for psychiatric disorders. Issue 1 (16th April 2015) - Chhabra, Harleen; Shivakumar, Venkataram; Agarwal, Sri Mahavir; Bose, Anushree; Venugopal, Deepthi; Rajasekaran, Ashwini; Subbanna, Manjula; Kalmady, Sunil V.; Narayanaswamy, Janardhanan C.; Debnath, Monojit; Venkatasubramanian, Ganesan
Abstract : Background and Aim: Transcranial direct current stimulation (tDCS) is a non-invasive and well-tolerated brain stimulation technique with promising efficacy as an add-on treatment for schizophrenia and for several other psychiatric disorders. tDCS modulates neuroplasticity; psychiatric disorders are established to be associated with neuroplasticity abnormalities. This review presents the summary of research on potential genetic basis of neuroplasticity-modulation mechanism underlying tDCS and its implications for treating various psychiatric disorders. Method: A systematic review highlighting the genes involved in neuroplasticity and their role in psychiatric disorders was carried out. The focus was on the established genetic findings of tDCS response relationship with BDNF and COMT gene polymorphisms. Result: Synthesis of these preliminary observations suggests the potential influence of neuroplastic genes on tDCS treatment response. These include several animal models, pharmacological studies, mentally ill and healthy human subject trials. Conclusion: Taking into account the rapidly unfolding understanding of tDCS and the role of synaptic plasticity disturbances in neuropsychiatric disorders, in-depth evaluation of the mechanism of action pertinent to neuroplasticity modulation with tDCS needs further systematic research. Genes such as NRG1, DISC1, as well as those linked with the glutamatergic receptor in the context of their direct role in the modulation of neuronal signalling related to neuroplasticity aberrations, are leading candidates for future research in this area. Such research studies might potentially unravel observations that might have potential translational implications in psychiatry.